2019
DOI: 10.1371/journal.pone.0225503
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of parenting interventions for the prevention of behaviour problems in children

Abstract: BackgroundBehavior problems are common among children and place a high disease and financial burden on individuals and society. Parenting interventions are commonly used to prevent such problems, but little is known about their possible longer-term economic benefits. This study modelled the longer-term cost-effectiveness of five parenting interventions delivered in a Swedish context: Comet, Connect, the Incredible Years (IY), COPE, bibliotherapy, and a waitlist control, for the prevention of persistent behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 47 publications
0
10
0
1
Order By: Relevance
“…They also assumed that the intervention effect gradually decreased with a specified decay rate. A decay rate of 50% was commonly used in included studies [ 46 , 52 , 58 , 73 ]. Another common assumption to extrapolate the long term intervention effectiveness was that considering the interventions run over the time horizon [ 33 35 , 50 , 67 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also assumed that the intervention effect gradually decreased with a specified decay rate. A decay rate of 50% was commonly used in included studies [ 46 , 52 , 58 , 73 ]. Another common assumption to extrapolate the long term intervention effectiveness was that considering the interventions run over the time horizon [ 33 35 , 50 , 67 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…In models with a shorter time horizon, only 22 studies (44.9%) justified the use of a shorter time horizon. In 27 Markov models, three studies (accounted for 11.0% of all Markov models) did not explicitly state the cycle length [ 47 , 50 , 52 ] and 11 studies (accounted for 40.7% of all Markov models) did not provide any justification for the chosen cycle length [ 31 , 34 , 44 – 46 , 48 , 57 , 58 , 60 , 61 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, parent‐based interventions effectively reduce childhood externalizing behaviour problems (Mingebach, Kamp‐Becker, Christiansen, & Weber, 2018). Long‐term economic evaluations have found that parent training as prevention and treatment of childhood conduct disorders are cost‐effective (Mihalopoulos, Sanders, Turner, Murphy‐Brennan, & Carter, 2007; Nystrand, Feldman, Enebrink, & Sampaio, 2019; O’Neill, McGilloway, Donnelly, Bywater, & Kelly, 2013; Sampaio et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Si se analiza más de cerca el formato de distribución de EPEC, sus cursos parentales se aplican a grupos de padres, con un formato interactivo y de aprendizaje colaborativo que incluye elementos clave como la observación, las representaciones de situaciones y los debates grupales. Según la evidencia empírica, no solo las intervenciones grupales son mejores en coste-beneficio (Nystrand et al, 2019), sino que también parecen disminuir los sentimientos de aislamiento de los padres (Tully et al, 2017). Cuando los padres desarrollan relaciones con familias que presentan problemas similares, parece reducirse el estigma de contar con un hijo problemático al tiempo que mejora la percepción que las familias tienen sobre el apoyo social (Tully et al, 2018).…”
Section: Antecedentes Teóricosunclassified